ANALISA PENERAPAN KONSEP LEAN SERVICE UNTUK MENINGKATKAN KEPUASAN KONSUMEN DI PT HONDA KJM (CABANG AHMAD YANI) - Hartadi Wijaya (Universitas Putera Batam, 2023)
Consumers want services that can bring their own satisfaction, so that consumers return to using these services. Basically the consumer satisfaction in the quality of service, service satisfaction is used to make a service system optimal and effective. The problem of waste in service at PT Honda KJM (Ahmad Yani Branch) is found in the long waiting time for the service process from 10.00 to 11.35 in the afternoon and motorbike maintenance which depends on the level of difficulty, with lean service the service will be better than before, and will add to the profit for the service company. Lean Service by definition are methods and equipment designed to reduce costs, improve performance, reduce waiting times, eliminate waste, so that service quality can be maximized. Where lean service is used for a service approach that ensures information that can be conveyed to consumers directly and maximally in getting service. The principle of lean service has been commonly used in the manufacturing industry, but over time, the service industry has begun to adapt this principle to reduce waste in service companies.